Comparison of design experiment in carbon dioxide (co2) corrosion prediction - Feng, Cheng (2013)
The excellent of mechanical properties and lower cost make carbon steel, low alloy steel, become the main structural material used in oil and gas industry. CO2 corrosion is a common and serious problem. Every year, the CO2 corrosion causes failure with a great loss. There are many factors influence CO2 corrosion such as flow rate, CO2 concentration, pH, temperature, pressure and material property. Base on the factors which affect in model calculation. Some of the models predict corrosion rates based on different parameters and assumptions. So, it can produce different results under the same cases. Consequently, data taken from the model can be over prediction or less prediction. The objective of the study is to compare the CO2 predictive models calculated by several experimental design models (CRD, FFD, TM and RSM). Investigate the effects on carbon steel corrosion in CO2 environment combination with pH, temperature, and flow. Application several designs of experiments are important to simplify CO2 corrosion behavior